37. Intercomparison in digital angiography: Low contrast detectability and air kerma data collection from digital radiology AIFM working group members. (December 2018) - Paruccini, N.; Villa, R.; Giordano, C.; Soavi, R.; Colombo, P.; De Mattia, C.; Rottoli, F.; Nici, S.; Origgi, D.; Emiro, F.; D'Ercole, L.; Mantovani, L.; et al.
Abstract : Purpose: The aim of this study is to collect Statistical Low Contrast Detectability (LCD)[1] data from different angiography using the same phantom and the same software for the analysis. Data from this study will define the reference value and the tolerance for quality control tests. Methods: A phantom consisting of a square aluminum target and a 5-step-wedge (0.25–1.25 mmAl) was built. A Matlab software automatically calculates LCD values in terms of Pixel Value (PV) and contrast threshold (Cth); it also converts PV in mmAl, providing the LCD (mmAl). Phantoms and software have been distributed to the members of AIFM digital radiology working group. A simple protocol has been followed by all the physicists. Two different set up for Low Contrast Detectability measurement have been defined using, at least, two different attenuation phantoms: 16 cm PMMA phantom and 1.5 mmCu filter. Different acquisition protocols were used and LCD phantom has been employed in different modalities such as fluoroscopy, fluorography and DSA. Dosimetric data has been also collected. Results: This method is able to collect low contrast detectability information from different modalities, clinical protocols and equipment by different vendors. Preliminary results have been reported inTable 1 . Conclusions: The LCD phantom and statistical method can be easily implemented in angiography. Data from this study can be used to define the reference value and the tolerance for low contrast threshold quality control in digital angiography with flat panel detector. The same method can also be applied in mammography, CR and DR radiography.